Implementing Kinperma Media to Improve Third-Grade Students’ Mathematics Learning Outcomes in Islamic Elementary Schools - Ali Ridlo; Dewi Arifah; Dewi Kartika Sari; Muhammad Luthfi Efendi; Nurul Agustin (Information Technology and Science (ITScience), 2026)
This study aims to improve the mathematics learning outcomes of third-grade students at MI Al-Azhar Menganti Gresik through the application of Kinperma (Mathematical Multiplication Wheel) media in multiplication learning. The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model, which was implemented in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 23 third-grade students in the 2025/2026 academic year. Data were collected through observations of teacher and student activities, learning outcome tests, and student response questionnaires, and analyzed using descriptive qualitative and quantitative techniques. The findings indicate a significant improvement in both the learning process and student achievement. Teacher activity increased from 83% in Cycle I (good category) to 93% in Cycle II (very good category), while student activity improved from 93% to 98%, both categorized as very good. Student learning outcomes also showed substantial progress, with classical learning mastery increasing from 48% in Cycle I to 87% in Cycle II. In addition, student responses toward the use of Kinperma media improved from 81% (good category) to 90% (very good category), reflecting increased motivation, interest, and understanding of multiplication concepts. These results demonstrate that Kinperma media effectively facilitates concrete, interactive, and student-centered learning aligned with the cognitive development characteristics of elementary school students. Therefore, Kinperma media is feasible and effective as an alternative instructional medium to enhance mathematics learning outcomes, particularly in multiplication materials at the elementary school level.